Role of PPAR-Α Signaling Pathway on the Protection of Antituberculosis-Induced Liver Damage by Purple Sweet Potato Extract - i gusti ayu artini (Journal of Global Pharma Technology, 2020)
Background: Peroxisome proliferator activated receptor-α (PPAR-α) participates in protecting the liver from many cases of liver damage. It is involved in reducing lipid accumulation, oxidative stress and inflammation. Purple sweet potato extract is one of herbal extract that posses hepatoprotector activity related to its antioxidant and antiinflammatory action. Its hepatoprotective effect on isoniazid and rifampicin induced hepatic injury has not been established yet, as well as its effect on PPAR-α expression and activation in the liver. The aim of this research was to investigate the hepatoprotective effect of purple sweet potato extract on hepatic injury induced by isoniazid and rifampicin, as well as the effect of purple sweet potato on PPAR-α expression and activation in the liver. Methods: The study design was randomized post test only control group design. We included male Wistar rats, age 8-12 weeks, weight 180-220 gram (divided into 3 groups: control, intervention and normal group). The extraction was performed with masseration technique. PPAR-α expression was measured with ELISA; activated PPAR-α was detected using immunohistochemistry; ALT level was measured with spectrophotometry. Data were analyzed using One Way Anova test, continued with Post Hoc test. Results: The result represented that PPAR-α expression in intervention group was significantly higher than control (1.344±0.249 vs. 0.587±0.306; p